(untitled) (Al-Mansour Journal, 2023)
The COVID-19 epidemic wreaked havoc on every area of human life, with severe consequences for all sectors of the global economy. The pandemic slowed and reversed advances in health, resulting in shorter life expectancy, particularly in poor and underdeveloped countries. Machine learning and artificial intelligence, on the other hand, played a significant role in the global response to the pandemic. As a result, the current research sought to evaluate the role of artificial intelligence and machine learning in tackling the threats posed by the COVID pandemic, intelligence and machine learning had a significant part in the response to the COVID-19 pandemic’s issues. Among other notable accomplishments, artificial intelligence, machine learning, and various digital communication tools through telehealth played important roles in scaling customer communications, providing a platform for understanding how COVID 19 spreads, and speeding up COVID-19 research and treatment. The takeaway is that, the role of artificial intelligence and machine learning motivates us to conclude that governments must build trust in these technologies in order to address future health issues and ensure that sustainable development goals related to good health and wellbeing are met.